A Thermodynamic Approach for Selection of Anodizing Electrolytes in Aluminium–Holmium System. Issue 6 (27th February 2020) - Shahzad, Khurram; Mardare, Cezarina Cela; Ionut Mardare, Andrei; Hassel, Achim Walter
Abstract: Invited for this month's cover picture is the group of Achim  Walter Hassel from Johannes Kepler University Linz (Austria). The cover picture shows the strategy involved in electrolyte selection for anodizing the Al–Ho system, based on combinatorial library screening by using scanning droplet cell microscopy. Read the full text of the Article at 10.1002/celc.201901634 . Abstract : "A thermodynamic approach is presented based on systemic simulation and superimposition of Eh–pH diagrams to rapidly identify the pH range and electrolytes for metallic alloy anodization. The applicability of this approach is verified on two metals and their selected alloys with different compositions and microstructures by using voltammetry, EIS, and corrosion studies…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.201901634 .